Sudden sensorineural hearing loss associated with electronic cigarette liquid: The first case in the literature. (November 2018) - Demir, Emine; Topal, Sevgi
Abstract: Pediatric sudden sensorineural hearing loss (SSNHL) is a quite rare otologic emergency. Etiology of SSNHL isn't enough clear. Electronic cigarette (EC) is a device that uses increasingly and it contain liquid which keep nicotin and various chemicals. This liquid can be ingested mistakenly by children and various side effects may develop. But hearing loss wasn't reported before as a side effect. We presented an interesting case, she was 6-year-old who developed bilaterally SSNHL associated with drinking electronic cigarette liquid.